Estudo comparativo da expressão imuno-histoquímica das proteínas Bcl-2, p53, caspase-3 e Ki-67 em hiperplasias fibrosas inflamatórias, queilites actínicas e carcinomas de células escamosas no lábio inferior - Balassiano, Karen Zavaro (2004)
The natural ultraviolet radiation has been identified as the main aetiology of skin and lip injuries. Actinic keratosis in lip or actinic cheilitis, according to World Health Organization, as a premalignant lesion of the labial cancer, is presented, clinically, as the first signal that damages had been caused to the lip, most of the times, irreparable, being able to develop, in its great majority, in a squamous cell carcinoma. The action of the ultraviolet radiation in the development of malignant injuries occurs through its direct action in the cells leading to the damage in its DNA allowing that they continue the mitotic cycle with defective genes. The disordered relation between proliferation and cellular death can, mostly, predict the evolution and behavior of these injuries, besides supplying important information of the tumoral progression. The aim of this work was to evaluate, immunohistochemically, the inhibiting and proliferate expression of apoptosis and cellular proliferation proteins as, p53, mutate p53, Bcl-2, Ki-67 and caspase-3 in 20 cases of inflammatory fibrous hyperplasia, 20 of actinic cheilitis, being four with epithelium dysplasia and 20 of squamous cells carcinoma, all located in lower lip. The results had presented that the identification of proteins p53 (DO-7) and mutate p53 (PAb-240) had shown increasing with the progression of the injuries in the suprabasal region with diffuse distribution, as the Bcl-2 protein. Significant descriptive and quantitative difference were observed between proteins p53 (DO-7) and mutate p53 (PAb-240) in the three analyzed groups, showing that antibody DO-7 revealed a higher expression than the PAb-240. The antibody Ki-67 revealed high expression of the protein in the suprabasal region of all the groups although had not presented significant difference between them. The cases of cheilitis with and without epithelium dysplasia had disclosed a significant difference only for the markers mutate p53 (PAb-240) and Bcl-2. The xpression of these markers and p53 (DO-7) had shown higher in the cases without epithelium dysplasia. The expression detected in this study for these markers in all the lesions suggests that the loss of the regulation of apoptosis and the cellular proliferation also occurs in an initial phase of the development of the premalignant lesions included those where morphologically it is not possible to detect any alteration. These data show the importance of the immunomarkers study involved in bucal carcinogenesis for evaluation of the prognostic of premalignant and malignant lesions and the indication of more efficient therapeutical and preventive procedures.